HUBUNGAN ANTARA PENERAPAN PRINSIP ETIKA LINGKUNGAN DAN SIKAP PEDULI LINGKUNGAN MAHASISWA - Eka Imbia Agus Diartika (Integrative Perspectives of Social and Science Journal, 2024)
Biology students who are supposed to be promoters in preserving the environment still lack environmental ethics and care for the environment. The purpose of this study is to know the application of the principles of environmental ethics, environmental care attitude, and the relationship between the application of environmental ethics principles and caring attitude towards the environment of Biology students at the State University of Malang. This type of research is descriptive correlational by analyzing the relationship between the application of environmental ethics principles and the environmental care attitude of Biology S1 students in Malang State University. The application of environmental ethics principles in the UM biology department is 7 people (14%) have applied the principles of environmental ethics well and 43 people (86%) have applied the principles of environmental ethics very well. The attitude of caring for the environment in the UM biology department is 18 people (36%) who have a good environmental care attitude and 43 people (86%) have a very good environmental care attitude. The relationship between the application of environmental ethics principles and the caring attitude of biology students in the State University of Malang amounted to 0.003 <0.01 based on Spearman Correlation calculations, so there was no correlation between the application of environmental ethics principles and environmental care attitude towards biology students at the State University of Malang. Thus, the higher environmental ethics does not necessarily make the attitude of caring for biology students of Malang State University higher.